Analisis Pendapatan dan Faktor-Faktor yang Mempengaruhi Pendapatan Usaha Emping Melinjo - Suminar, Yuyum; Dwirayani, Dina; Trisnaningsih, Umi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
This study aims to find out: (1) The cost of emping melinjo business. (2) Business income emping melinjo. (3) What factors affect the business income of emping melinjo. The method used in this study is quantitative research method. The population in this study is emping melinjo business actors in Tuk Village, Kedawung District, Cirebon Regency. The sampling technique in this study was to use a simple random sampling technique as many as 52 business actors were sampled. The data analysis technique used are classical assumption test and multiple linear regression using SPSS 22 aplication. The results showed that: (1) The costs incurred for fixed costs and variable costs were RP 85,531/month and RP 16.302.433/month respectively with total costs of Rp 16.387.964/month and average receipts of Rp 19.119.519/month. (2) Average income of Rp 2.731.556/month and worth working on with an R/C ratio of 1.18. (3) Factors that affect emping melinjo business income are selling price, raw material price, and length of business. The results of this study are useful for emping melinjo business actors in order to increase business income.